Sabrina Sue loves the sea - Burris, Priscilla (Ready-to-read. Star reader!., 2021)
Little chicken Sabrina Sue lives on a farm but dreams of the sea, and despite the other farm animals telling her she is ridiculous and silly, she decides to set out on an adventure to finally see the ocean.